Development and psychometric properties of a self-medication behavior inventory - Penagos-Corzo, Julio C.; Ortiz-Barrero, Melissa J.; Hernández-Ramírez, Reneé; Ochoa-Ramírez, Yavne; González Ehlinger, Regina; Pérez-Acosta, Andrés M. (Frontiers in Psychology, 2024)
The psychometric properties of a scale created to analyze self-medication behavior were evaluated. In a binational study between Colombia and Mexico, 779 participants responded to the Self-Medication Behavior Inventory (SMBI-9) and four other inventories in order to verify concurrent validity. Significant relationships were found between the SMBI-9 factors and the inventories used for concurrent validity. Confirmatory analysis yielded a model of optimal fit (CFI = 0.995, TLI = 0.991), in the proposed four-factor model: a) Social influence, b) Attitude toward medicine, c) Avoidance, and d) Prevention. Analyses showed that the SMBI-9 is invariant between the two national samples. Differences were identified in the "Avoidance" factor according to whether participants had health insurance and also according to gender. On the other hand, the factor "Social Influence" showed differences according to level of schooling.